KADERISASI ULAMA PEREMPUAN DI JAWA TENGAH - Hatta Abdul Malik (At-Taqaddum, 2012)
Islamic Boarding school as an institution of clerical/Muslim leader cadre’s  since 1970 has opened up education for female student’s (santriwati) until now. The amonth of santriwati learning in Islamic boarding school also not inferior to male students there. however, very few women of muslim leader compared the presence of male muslim leader who very much. From the results of this research note that the lack of presence of scholars of women due to several factors : (1) there are still many Islamic boarding school (Kyai, male students and female students Santriwati) which looked at women in the domestic realm can not be a family leader, (2) Women in the social sphere have the same rights with men, although some have argued should not be, (3) In the realm of religious women get very dogmatis position. Although the schools curriculum provide the same education between men and women, but in practice is still found gender bias. Santriwati inability to resolve to resolve the problem, still require the help of male student. Deviciencies of curriculum schools, there are not special education for women to dare to came and be a driver in front of people.